Developing Mystery Box Vocabulary (MBV) Media Based on the Problem-Based Learning Model to Increase the Mastery of Vocabulary of Various Objects in Primary School - Fitriana, Rizka; Purwati, Panca Dewi; Trimurtini (Universitas Muhammadiyah Malang, 2024)
This research was motivated by students' need for more vocabulary mastery due to media and models that did not attract students' interest in learning, coupled with teachers' teaching models that still used the lecture method. This research is development research using the Research and Development model, including eight stages. This development research aims to test the feasibility and effectiveness of mystery box vocabulary media based on a problem-based learning model. The data collection methods used were observation, interviews and teacher and student needs questionnaires, pre-posttests, media and material validation sheets for media experts and material experts, as well as teacher and student response questionnaires regarding the suitability of the mystery box vocabulary media. The results of this study show that the average value.The media validity test obtained was 85% with very decent qualifications and material validity was 96% with very decent qualifications. The results of trials using large groups showed an increase in student learning outcomes with an average N-Gain of 0.826 and significance (2-tailed) < 0.05. Based on this analysis, it can be concluded that the mystery box vocabulary media based on the problem-based learning model developed on material for mastering the vocabulary of various objects is declared suitable and effective for use in class II at SDN 3 Jepon, Blora.